2019
DOI: 10.1111/ejn.14368
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal activation of 5‐HT1B receptors and BDNF production by vagus nerve stimulation in rats under chronic restraint stress

Abstract: A growing body of evidence shows that the electrical stimulation of the vagus nerve can improve mental illness including depression. Here, we investigated whether the vagus nerve stimulation (VNS) is involved in regulating the responsiveness of hippocampal neurons in rats under chronic restraint stress (CRS). c‐Fos protein signals were detected 2 hr after VNS in 5‐HT1A receptor‐positive neurons in the dorsal raphe nucleus (DRN) as well as in the nucleus tractus solitarius (NTS). Chronic VNS was performed on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 55 publications
1
28
0
1
Order By: Relevance
“…We have previously demonstrated that sham needle stimulation around ST36 can partially induce acupuncture-like responses such as the induction of α6 integrin at the stimulation site or increased expression of GAP-43 and Erk1/2 in the dorsal root ganglion (DRG). 15,30 Transcutaneous electrical stimulation and EA show similar effectiveness in the regulation of gastric motility in humans. 31 We therefore speculate that acupuncture needle stimulation may have varying anti-inflammatory effects depending on subcutaneous locations (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously demonstrated that sham needle stimulation around ST36 can partially induce acupuncture-like responses such as the induction of α6 integrin at the stimulation site or increased expression of GAP-43 and Erk1/2 in the dorsal root ganglion (DRG). 15,30 Transcutaneous electrical stimulation and EA show similar effectiveness in the regulation of gastric motility in humans. 31 We therefore speculate that acupuncture needle stimulation may have varying anti-inflammatory effects depending on subcutaneous locations (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Electrical current (10 mA, 5 Hz, pulse duration: 5 ms, A-M Systems) was delivered for 5 min, as described in our previous report. 15…”
Section: Methodsmentioning
confidence: 99%
“…The electrical current (10 mA, 5 Hz, 5 ms of pulse duration, 5 min) was applied by using the isolated pulse stimulator (model 2100, A-M Systems Inc., Sequim, WA, USA). Our previous study showed that the same stimulation protocol for the acute and chronic VNS at the cervical level was effective to induce the activation of neurons in the dorsal raphe nucleus and the hippocampal neurons in rats (Shin et al 2019). After hVNS, the abdomen was closed by 5-0 nylon suture, and animals were returned to animal room and sacrificed 1-3 days later.…”
Section: Vagus Nerve Stimulation and Hepatic Vagotomymentioning
confidence: 99%
“…Exposed nerve was placed in a bipolar hook electrode of nichrome wire, and the electrical current (10 mA, 5 Hz, 5 ms of pulse duration, 5 min) was applied by using the isolated pulse stimulator (model 2100, A-M Systems Inc., Sequim, WA, USA). We used this stimulation condition based on our previous study showing an e cient induction of AFVN leading to activation of hippocampal neurons (Shin et al 2019). After hVNS, animals were returned to animal room and sacri ced 1 -3 days later.…”
Section: Vagus Nerve Stimulationmentioning
confidence: 99%